Analisis Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan: Pada Perusahaan yang tergolong IDXQ30 di BEI Periode 2018 - 2021 - Nabila Tsabita Mustarih; Akhmadi (CV ODIS, 2023)
The role that investors play in the current rapid development of the Indonesian Stock Exchange, investors must be very careful when making investments and must research the companies they wish to support. According to Mahendra (2018), a company is founded with a specific purpose and the main goal is to maximize profits. While the goal of the third company is to increase the value of the company, which is reflected in the share price, the goal of the second company is to enrich its shareholders or shareholders. The business has released its financial reports for the years 2018 to 2021. A total of thirty companies failed to comply with the requirements in the incomplete financial statements from 2018 to 2021. Therefore, using the SPSS application version 26, a binary logistic regression analysis was performed on the data collected by 25 sample companies. The type of data used in this research is secondary data and quantitative data. The company's financial reports can be accessed on the IDX, which is the source of study data. 2. The profitability of a company is directly inversely correlated with its value. Directly proportional to the profitability of the company, and vice versa, the value of the company increases. 3. The size and profitability of a company is directly related to its value.